The Jordan-Postnikov Normal Form of a Real Linear Operator - Dalalyan, Samvel (Armenian Journal of Mathematics, 2008)
We give a direct proof of the following result: for any real linear operator there exists a basis in which it has a Jordan-Postnikov matrix. This matrix for a real linear operator is determined uniquely up to the order of direct summands on the diagonal.